Hitting the Jackpot: Reaching up to 10000 BBL through Simson Idle Well Reactivation Strategy - Purnomo, Simson; Kristanto, Dedi; Suhascaryo, Nur (Journal of Petroleum and Geothermal Technology, 2025)
This study seeks the effective reactivation strategy of the Simson idle well in the Purnomo oilfield PT Pertamina EP Cepu to produce free-emulsion oil with low costs and technical risks. DCA and Pipesim were used to calculate the production forecast, the precise choke, and the flow coefficient. Due to its remote location, a rig-less and naturally flowing well minimized the cost. A modified choke manifold compliant with the API 6A was installed to control the flow rate from the annulus to the Tank on Site (TOS). The cumulative production in 2023 reached 10.961 bbl with the average BSW at 2%. To avoid water coning, the well should be operated under the critical rate of 60 BFPD.  To maintain stable production, the optimum flow coefficient was Cd 0.838 by installing the first 5-mm choke and the second 8.7-mm choke. The average daily production rate by intermittent flow i.e. of 5-hour production and 19-hour shut-in well was 34 blpd, 33 bopd with water cut at 1.64%. By the end of the PSC contract in 2035, the production forecast value using the choke manifold can reach 81 MSTB – 50 MSTB higher than the SRP method. Keywords: idle well reactivation, flow coefficient, choke manifold